Raising Tolerant Attitude to Children - Chairilsyah, Daviq (Aulad: Journal on Early Childhood, 2019)
This paper aimed to provide logical reasons for parents and teachers about the importance of teaching tolerance from early age. This paper explained the types of tolerance that should be trained such as religious tolerance, tolerance of multi-ethnicity, multiracial, cultural and gender differences. Literature review was used in explaining theoretical studies, and discussion. The steps of writing a literature review are: 1) Finding data that fits the purpose. 2) Identifying data. 3) Choosing data of writing the article. 4) Formulate, create and assess the quality of writing articles. 5) Synthesize the writing scientific articles. Teaching it from an early age can create children who are able to respect others and do not distinguish. Parents and family members are the main facilitators for children to cultivate an attitude of tolerance. Parents are required to teach tolerance starting from the family environment to the wider community. Meanwhile, the teacher can teach from the social environment to fellow students at school. It can be concluded that the role of parents and teachers here is very important in the inculcation of attitude and tolerance in early childhood